2016
DOI: 10.1021/acsami.5b08315
|View full text |Cite
|
Sign up to set email alerts
|

Nanopattern Gradients for Cell Studies Fabricated Using Hole-Mask Colloidal Lithography

Abstract: Culturing cells on gradient nanopatterns provides a useful tool to explore cellular adhesion to mimics of the extracellular matrix or screen for cellular responses to nanopatterns. A method is presented to fabricate complex gradient protein patterns based on hole-mask colloidal lithography, which can generate nanopatterns in multiple materials and of multiple shapes. Gradients of gold structures were functionalized to form gradients of protein nanopatterns of different shapes (bars, dot pairs, and rings), wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…[121][122][123] For example, it was shown that spreading and cytoskeleton organization of C2C12 myoblasts increased along topographical gradients of different nanopatterns (bars, rings and dot pairs) functionalized with vitronectin, and that the pattern length, but not its area, was the critical parameter for cell spreading. 122 On a parallel gradient of BSA/lysozyme and surface roughness in the nano-scale, fibroblasts showed increased cell adhesion in direction of the gradient. 123 Osteoblasts, however, showed decreased spreading and proliferation along a uniformly RGD-decorated nanoparticle-density gradient.…”
Section: Combinatorial Gradients Of Biochemical Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[121][122][123] For example, it was shown that spreading and cytoskeleton organization of C2C12 myoblasts increased along topographical gradients of different nanopatterns (bars, rings and dot pairs) functionalized with vitronectin, and that the pattern length, but not its area, was the critical parameter for cell spreading. 122 On a parallel gradient of BSA/lysozyme and surface roughness in the nano-scale, fibroblasts showed increased cell adhesion in direction of the gradient. 123 Osteoblasts, however, showed decreased spreading and proliferation along a uniformly RGD-decorated nanoparticle-density gradient.…”
Section: Combinatorial Gradients Of Biochemical Componentsmentioning
confidence: 99%
“…Thus, control over the surface properties is possible, because mechanical and topographical 38 functionalization use inherently different fabrication steps than biochemical ones. Surface topography on the one hand can be produced by a wide variety of methods, including different lithographical approaches 122,126,156 , microcontact printing , multiphoton excited photochemistry 121 , particle adsorption 111,124 , sandblasting 119 , different etching techniques 116,126,130,133 , laser ablation methods 129 , mold casting methods 120,[126][127][135][136][137] , embossing 132,134 or electrospinning 142,147,[204][205] . Modification of mechanical properties on the other hand is usually achieved by employing mechanically diverse polymer substrates that can be generated for example from polyethylene glycol (PEG) 63,157 , PDMS 163 , collagen-GAG 168 or hyaluronic acid 186 combined with poly-L-lysine 165,167 or poly(acrylamide-co-acrylic)acid 158 by varying the appropriate cross linker amount.…”
Section: Materials Functionalization With Various Biochemical Groupsmentioning
confidence: 99%
“…For example, UV grafting has been performed using a UV-resistant mask, which confines the polymerization in desired regions on the surface . Chemical vapor deposition (CVD) techniques, including plasma polymerization, , sputtering, and physical vapor deposition have been combined with mask-based technologies. For example, colloidal masks and plasma polymerization have been used together for generating chemical patterns.…”
Section: Multichemical Signalsmentioning
confidence: 99%
“…Based on colloidal lithography, Sutherland and colleagues fabricated complex spacing gradient protein nanopatterns of three different shapes (bars, dot pairs and rings), where the size of the nanostructures varied from 160 to 200 nm . Cells growing on the vitronectin nanopatterns showed differential adhesion (spread area/focal adhesion size) along the gradients.…”
Section: Techniques Of Micropatterning and Nanopatterningmentioning
confidence: 99%